Quarterly screening optimizes detection of sexually transmitted infections when prescribing HIV preexposure prophylaxis. (1st July 2020) - Tang, Eric C.; Vittinghoff, Eric; Philip, Susan S.; Doblecki-Lewis, Susanne; Bacon, Oliver; Chege, Wairimu; Coleman, Megan E.; Elion, Richard; Buchbinder, Susan; Kolber, Michael A.; Liu, Albert Y.; Cohen, Stephanie E.
Abstract : Objective: The optimal screening frequency of sexually transmitted infections (STIs) for MSM and transgender women (TGW) on HIV pre-exposure prophylaxis (PrEP) is unclear, with present guidelines recommending screening every 3–6 months. We aimed to determine the number of STIs for which treatment would have been delayed without quarterly screening. Design: The US PrEP Demonstration Project was a prospective, open-label cohort study that evaluated PrEP delivery in STI clinics in San Francisco and Miami, and a community health center in Washington, DC. In all, 557 HIV-uninfected MSM and TGW were offered up to 48 weeks of PrEP and screened quarterly for STIs. Methods: The proportion of gonorrhea, chlamydia, and syphilis infections for which treatment would have been delayed had screening been conducted every 6 versus every 3 months was determined by taking the number of asymptomatic STIs at weeks 12 and 36 divided by the total number of infections during the study follow-up period for each STI. Results: Among the participants, 50.9% had an STI during follow-up. If screening had been conducted only semiannually or based on symptoms, identification of 34.3% of gonorrhea, 40.0% of chlamydia, and 20.4% of syphilis infections would have been delayed by up to 3 months. The vast majority of participants (89.2%) with asymptomatic STIs reported condomless anal sex and had a mean of 8.1 partners between quarterly visits. Conclusions: Quarterly STI screening among MSM on PrEP could prevent a substantial number of partners from being exposed to asymptomatic STIs, and decrease transmission.